Relationships Human and Divine: Retribution and Repentance in Children’s Lives, 1740–1870 - Martin, Mary Clare (Studies in church history, 2004)
The place of repentance and retribution in children’s lives between 1740 and 1870 has not been viewed positively. E. P. Thompson famously claimed that ‘the child’ in Methodist Sunday schools and in pious homes, from about 1780, was subjected to ‘the worst kind of emotional bullying to confess his sins and come to a sense of salvation’. In the 1840s children in the mines allegedly reported that they had been taught at Sunday school that hell was a place full of fire and brimstone. Nor have such assertions been made only about working-class children. Lawrence Stone, James Walvin, Walter Houghton and others claimed that the young of the middle and upper classes were intimidated by stories such as Mrs Sherwood’s The Fairchild Family, and other Evangelical tracts threatening hell and retribution and urging immediate repentance. In 1995, Hugh Cunningham still followed Stone’s chronology in suggesting that the early nineteenth century was a period of ‘reaction’ in religious terms for children.